International Conference on Intelligent Data Communication Technologies and Internet of Things (ICICI) 2018 - Hemanth, Jude.; Fernando, Xavier; Lafata, Pavel; Baig, Zubair; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses data communication and computer networking, communication technologies and the applications of IoT (Internet of Things), big data, cloud computing and healthcare informatics. It explores, examines and critiques intelligent data communications and presents inventive methodologies in communication technologies and IoT. Aimed at researchers and academicians who need to understand the importance of data communication and advanced technologies in IoT, it offers different perspectives to help readers increase their knowledge and motivates them to conduct research in the area, highlighting various innovative ideas for future research.
Security Effect on AES in Terms of Avalanche Effect by using Alternate S-Box -- Enhanced Portable Customer Experience Using Community Computation in Offline Retail -- Cluster-Based Wireless Sensor Networks Using Ant Colony Optimization -- A Study on Cross-Layer TCP Performance in Wireless Ad Hoc Network -- Hyper Elliptic Curve based Homomorphic Encryption Scheme for Cloud Data Security -- Support Vector Neural Network and Principal Component Analysis for Fault Diagnosis of Analog Circuits -- Performance Evaluation of Symmetric Block Cipher RC6 with ECB and CBC Operation Modes -- An Improved Block-based Motion Estimation Algorithm for Compressing a Video -- Hierarchical View on Detection of Attacks in Closed Loop Control Systems -- Facial Expression Recognition System for Visually Impaired -- A Systematic Mapping Study of Content Based Filtering Recommender Systems -- Named Entity Recognition in Marathi Language -- Self Configurable Air Pollution Monitoring System Using IoT and Data Mining Techniques -- Novel Defence Scheme for Phishing Attacks in Mobile Phones -- New Automated Vehicle Crash Avoidance System Based on Dipping and RF Techniques.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence